Are shorts equally informed? A global perspective - BOEHMER, Ekkehart (Institutional Knowledge at Singapore Management University, 2017)
Short selling predicts future stock returns globally. We use 11 short-sale measures to examine the informativeness of short sales in 38 countries for the July 2006 to December 2014 period. We find that different short-sale measures display different return predictability. The days-to-cover ratio and loan supply measures have the most robust predictive power in the global capital market. We also document significant cross-country differences in the predictive power of the short selling measures and find that return predictability is stronger in countries with mild forms of short-sale restrictions, better market quality, and more developed markets.